Business Model Canvas dan Social Media Marketing untuk Meningkatkan Kapasitas Pengusaha Mikro di Kabupaten Pangkep - Anugrayani Bustamin (Faculty of Engineering UNHAS, 2020)
Community service has been done to improve the performance and capacity of the Pelita Desa Farmers Group in Pangkep Regency. Pelita Desa Farmers Group is a group of